Faktor Pengaruh Perilaku Kerja Kontraproduktif pada Karyawan Account Officer Bank: Studi di PT. Bank XYZ di Kota Semarang - Muhammad Allam Nafiis; Eisha Lataruva (Faculty of Economics and Business Diponegoro University, 2025)
The important role of Account Officer (AO) as a bank energy marketing demands reliability in achieving targets, which not only contributes to the success of the company but also improves their synchronization, but pressure due to demands for quality service, technological changes, efficiency, and reduced work energy can trigger stress and dissatisfaction, which has the potential to cause deviant behavior in the workplace (CWB) such as avoiding work, sabotage, to failure, so this study focuses on understanding the root causes of the occurrence which are influenced by various factors such as Role Ambiguity, organizational constraints, and Job Burnout.The population in this study were all active employees of the Account Officer division of PT XYZ Tbk, Semarang City Branch. The selection of samples in this study used a sampling quota by adjusting the total number of Account Officer employees of PT XYZ Tbk, Semarang City Branch, as many as 56 people. Data was obtained by distributing questionnaires via Google Form. The data that has been collected will then be analyzed quantitatively using Structural Equation Modeling (SEM) with SmartPLS software version 4.0.The results of the study indicate that Role Ambiguity, Organizational Constraints, and Job Burnout are proven to have a positive and significant influence on Counterproductive Work Behavior (CWB), where role ambiguity experienced by Account Officers (AO) increases the possibility of task or internal neglect, limited organizational resources in the form of assistance and support for counterproductive behavior, and job burnout reduces AO involvement in work and increases the potential for actions that affect the organization, with this in line with previous studies showing that role ambiguity, organization, and high levels of burnout have a significant correlation with deviant behavior in the workplace.